2016
DOI: 10.1001/jamaoncol.2015.3638
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative Assessment of the Heterogeneity of PD-L1 Expression in Non–Small-Cell Lung Cancer

Abstract: Importance Early phase trials with monoclonal antibodies targeting PD-1/PD-L1 have demonstrated durable clinical responses in patients with NSCLC, however, current assays for the prognostic/predictive role of tumor PD-L1 expression are not standardized with respect to either quantity or distribution of expression. Objective In this study, we demonstrate PD-L1 protein distribution in NSCLC tumors using both conventional immunohistochemistry (IHC) and quantitative immunofluorescence (QIF), and compare results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
591
3
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 734 publications
(614 citation statements)
references
References 39 publications
16
591
3
4
Order By: Relevance
“…There are limited data on comparative studies published on assays that were not validated in trials, so they are of limited value, although they might forecast what we can expect when comparing the companion or complementary diagnostic assays. 17,18 The data generated from clinical trials validate both the efficacy of these drugs and the predictive performance of each allied biomarker assay as it was performed during each of the trials. In this era of evidence-based medical practice, to what extent can we afford to deviate from what was validated in the trials while there is no evidence to support doing so?…”
Section: At Least 4 Drugs At Least 4 Biomarkers?mentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited data on comparative studies published on assays that were not validated in trials, so they are of limited value, although they might forecast what we can expect when comparing the companion or complementary diagnostic assays. 17,18 The data generated from clinical trials validate both the efficacy of these drugs and the predictive performance of each allied biomarker assay as it was performed during each of the trials. In this era of evidence-based medical practice, to what extent can we afford to deviate from what was validated in the trials while there is no evidence to support doing so?…”
Section: At Least 4 Drugs At Least 4 Biomarkers?mentioning
confidence: 99%
“…A recent study comparing 2 commercially available clones, both developed as LDTs, based upon a SP142 clone (Spring Bioscience, Pleasanton, California) and the E1L3N clone (Cell Signaling Technologies, Boston, Massachusetts), demonstrated significant differences in staining performance. 18 Even if the very extensive technical validation that would be required to create an LDT were completed, there is still no guarantee of equivalent clinical predictive performance.…”
Section: Pd-l1 Immunohistochemistry-one Test?mentioning
confidence: 99%
“…Given that the FDA-approved Dako 22C3 companion diagnostic became available only in October of 2015 and that the 22C3 clone cannot be purchased apart from the approved kit, many laboratories have already technically validated other readily available and far less costly commercial antibodies as laboratory-developed tests (LDTs). Efforts to compare the performance of 2 commonly used antibody clones, E1L3N from Cell Signaling Technology and Ventana-SP142 (anticipated to serve as part of the companion diagnostic for atezolizumab), have demonstrated fair to poor concordance 16 ; however, these studies are limited by outdated antibody optimization techniques and the lack of a clear clinical gold standard in the form of response data. The importance of this latter issue cannot be understated.…”
mentioning
confidence: 99%
“…Sampling errors, tumoral heterogeneity, or testing of tissue obtained at diagnosis rather than at time of progression or relapse may underestimate or overestimate the percentage of neoplastic cells showing PD-L1 expression. 16,19 There is evidence across different tumor types that mutational signatures, neoantigen burden, and expression of other checkpoint inhibitors may predict response to immunotherapies. 20 It is quite possible that in the future another assay may supersede PD-L1 IHC as the biomarker of choice, assuming these markers can be validated in samples of past or future trials involving these immunotherapy drugs.…”
mentioning
confidence: 99%
“…This demonstrated that PD-L1 expression level is useful in enriching a population who would gain more from atezolizumab, but at the same time, proved itself as an imperfect biomarker in dichotomizing patients in treatment selection. The finding of observing response in tumors with low PD-L1 expression is further complicated by the high degree of intratumoral heterogeneity in NSCLC, which renders the PD-L1 expression level detected in biopsy specimens unrepresentative of whole tumor sample (8).…”
mentioning
confidence: 99%